Holm Oak Somatic Embryogenesis: Current Status and Future Perspectives - Martínez, María Teresa; San-José, María del Carmen; Arrillaga, Isabel; Cano, Vanesa; Morcillo, Marián; Cernadas, María José; Corredoira, Elena (Frontiers in Plant Science, 2019)
Quercus ilex (holm oak) is one of the most representative trees in the Mediterranean basin, but now the sustainability of its ecosystems is at serious risk due to the lack of natural regeneration and to the presence of a severe disease called oak decline that has caused the death of thousands of trees. The application of biotechnological tools, such as somatic embryogenesis, allows programs of genetic improvement of the species to be speeded up and helps in the conservation of its ecosystems. Somatic embryogenesis is currently considered one of the main biotechnological techniques that has demonstrated significant benefits when has applied to forest tree species, providing significant advantages such as mass propagation, genetic transformation, application of synthetic seed, and cryopreservation of elite genotypes. In this report, the state of the art of somatic embryogenesis in holm oak is reviewed. Factors affecting the induction (plant donor age, type of explant, or plant growth regulators) and maintenance and proliferation of the embryogenic cultures are summarized. Advances on the conversion of somatic embryos into plants and on the acclimatization of these plantlets, as well as the results obtained on the application of the genetic transformation and the cryopreservation procedures to holm oak embryogenic cultures, are also presented.